Poznańska szkoła językoznawstwa historycznego - Migdał, Jolanta; Piotrowska-Wojaczyk, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
The article presents Poznań school of historical linguistics. The founder of the school is Władysław Kuraszkiewicz. The schools’ central idea is a scholarly attitude which is based on respect for material, philological akribeia (accuracy) and caution in drawing conclusions. The representatives of this school are characterised by aspiration for measurability of research results and understanding of the role of statistics. Research is conducted on the carefully selected, very extensive material taking into account numerous variable features: chronological, geographic, generic, stylistic or formal. Among the scholars who must be included in this school are the disciples of Professor Kuraszkiewicz: Zdzisława Krążyńska, Tadeusz Lewaszkiewicz, Leszek Moszyński, Wojciech Ryszard Rzepka, Tadeusz Skulina, Bogdan Walczak and Tadeusz Zdancewicz. Nowadays, their disciples form another generation of scholars connected with Poznań school of historical linguistics.